Rhetoric and policy learning: On Rhodri Morgan’s ‘Clear Red Water’ and ‘Made in Wales’ health policies - Moon, David S (Public policy and administration, 2013)
One of the benefits of multi-level systems of governments, according to their supporters, is that their plurality of governmental institutions/levels provides the scope for valuable policy innovation and learning. One vocal supporter of this view has been former Labour First Minister of Wales (2000–2009) Rhodri Morgan, who labelled the United Kingdom’s devolved bodies “laboratories” for the formulation of new ideas to be subsequently shared and learnt from across the Union. An issue which has yet to be discussed, however, is the underappreciated but nevertheless important role played by the rhetoric of key actors such as Morgan in facilitating such a culture of policy learning. This article focuses upon this subject, looking at rhetoric as a factor in policy transfer through an analysis of the governmental language of Morgan himself. Specifically, it analyses the rhetoric through which his administrations’ health policies – which radically diverged from those followed at Westminster – were justified and described. It argues, in so doing, that Morgan’s administrations adopted a non-universal rhetoric of national (Welsh) specificity based around phrases such as “Made in Wales” and “Clear Red Water” politics to justify their policy programme, which may have actually delimited rather than facilitated possibilities for cross-border learning. Policy makers aiming to promote cross-polity institutional learning, it concludes, would do well to learn from the case of Morgan’s Labour administrations and avoid the dangers of nation-bounded rhetoric.